Tumor-associated macrophages regulate gastric cancer cell invasion and metastasis through TGFβ2/NF-κB/Kindlin-2 axis - Wang, Zhu (Chin J Cancer Res, 2020)
OBJECTIVE: Recent studies have shown that tumor-associated macrophages (TAMs) play an important role in cancer invasion and metastasis. Our previous studies have reported that TAMs promote the invasion and metastasis of gastric cancer (GC) cells through the Kindlin-2 pathway. However, the mechanism needs to be clarified. METHODS: THP-1 monocytes were induced by PMA/interleukin (IL)-4/IL-13 to establish an efficient TAM model in vitro and M2 macrophages were isolated via flow cytometry. A dual luciferase reporter system and chromatin immunoprecipitation (ChIP) assay were used to investigate the mechanism of transforming growth factor β2 (TGFβ2) regulating Kindlin-2 expression. Immunohistochemistry was used to study the relationships among TAM infiltration in human GC tissues, Kindlin-2 protein expression, clinicopathological parameters and prognosis in human GC tissues. A nude mouse oncogenesis model was used to verify the invasion and metastasis mechanisms in vivo. RESULTS: We found that Kindlin-2 expression was upregulated at both mRNA and protein levels in GC cells cocultured with TAMs, associated with higher invasion rate. Kindlin-2 knockdown reduced the invasion rate of GC cells under coculture condition. TGFβ2 secreted by TAMs regulated the expression of Kindlin-2 through the transcription factor NF-кB. TAMs thus participated in the progression of GC through the TGFβ2/NF-κB/Kindlin-2 axis. Kindlin-2 expression and TAM infiltration were significantly positively correlated with TNM stage, and patients with high Kindlin-2 expression had significantly poorer overall survival than patients with low Kindlin-2 expression. Furthermore, Kindlin-2 promoted the invasion of GC cells in vivo. CONCLUSIONS: This study elucidates the mechanism of TAMs participating in GC cell invasion and metastasis through the TGFβ2/NF-κB/Kindlin-2 axis, providing a possibility for new treatment options and approaches.